2014
DOI: 10.1136/bcr-2014-011255
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous closure of a dural arteriovenous fistula

Abstract: Spontaneous closure of a dural arteriovenous fistula (dAVF) is a rare condition and only a few cases have been reported since its first description in 1976. We report delayed and progressive spontaneous closure of a dAVF after massive intracerebral hemorrhage documented by angiographic studies before and after bleeding. To our knowledge, this is the first report to document gradual closure of a dAVF by serial angiographic studies. The mechanism of spontaneous closure of dAVFs has not been fully elucidated. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…[ 21 ] From the results of our systematic review, 12 other cases also posit a similar mechanism as the sole or primary factor behind the disappearance of their respective DAVFs. [ 3 , 8 , 14 , 16 , 17 , 24 , 25 , 28 , 30 ] In a report by Kannath et al .,[ 14 ] the authors speculated that DAVFs with sparse angioarchitectural networks were associated with spontaneous thrombosis and regression of DAVFs; similarly, Voormolen et al . [ 30 ] posited that small fistulas with single draining veins were more susceptible to venous outflow obstruction and subsequent lesion thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 21 ] From the results of our systematic review, 12 other cases also posit a similar mechanism as the sole or primary factor behind the disappearance of their respective DAVFs. [ 3 , 8 , 14 , 16 , 17 , 24 , 25 , 28 , 30 ] In a report by Kannath et al .,[ 14 ] the authors speculated that DAVFs with sparse angioarchitectural networks were associated with spontaneous thrombosis and regression of DAVFs; similarly, Voormolen et al . [ 30 ] posited that small fistulas with single draining veins were more susceptible to venous outflow obstruction and subsequent lesion thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…From our systematic review, the two main suggested mechanisms involve either direct endothelial injury and endoluminal stasis induced by neurosurgical intervention or thrombogenic effects of contrast medium during imaging. [ 2 , 3 , 7 , 10 , 16 , 26 , 28 , 30 ] A prototypical case reported by AlAfif et al . [ 3 ] documented both mechanisms in conjunction leading to the regression of the DAVF in their case: hematoma evacuation led to hemodynamic changes and partial closure of DAVF feeders, and subsequent follow-up angiographs contributed to chronic thrombosis and eventual regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If hematoma occurs and causes mass effect, the resulting compression on the feeding arteries could also explain the spontaneous resolution [4]. Recently, the gradual closure of a DAVF after a large intracerebral hemorrhage was documented by serial angiograms [5]. Contrast media given during digital subtraction angiography (DSA) can affect the endothelium of the feeding arteries and has been proposed as another possible explanation [6,7], though in high-flow lesions, the first-pass dwell time of contrast on the endothelium is minimal.…”
Section: Discussionmentioning
confidence: 99%
“…13 Pathological studies have demonstrated the expression of various vascular growth factors such as vascular endothelial growth factor in the dural layer and these factors may play a crucial role in the development of DAVF, especially in the setting of venous hypertension. 23,24 Beyond angiogenesis, vascular endothelial growth factor induces tissue factor, a major procoagulant which activates coagulation cascade and promotes fibrin deposition in the vessel wall.…”
Section: Observations and Implicationsmentioning
confidence: 99%